2012
DOI: 10.1113/jphysiol.2011.222414
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 5′‐diphosphate‐ribose is a neural regulator in primate and murine large intestine along with β‐NAD+

Abstract: Key points• Normal gastrointestinal activity depends upon orderly movement of nutrients and wastes through the alimentary canal. These movements require coordinated contractions of the muscular wall and regulation by excitatory and inhibitory motor neurons of the enteric nervous system. • We examined the nature of candidate purine neurotransmitters (ATP and β-NAD) and their metabolites (ADP and ADP-ribose) and the effects of these compounds on electrical and mechanical responses of colonic muscles.• After rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(126 citation statements)
references
References 43 publications
4
120
2
Order By: Relevance
“…However, responses to Up4A were much greater than responses to ADP, suggesting that ADP formation cannot explain the relaxation responses to Up4A. In contrast to Up4A, the relaxation to ADP likely is mediated by receptors in addition to P2Y1R (17).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…However, responses to Up4A were much greater than responses to ADP, suggesting that ADP formation cannot explain the relaxation responses to Up4A. In contrast to Up4A, the relaxation to ADP likely is mediated by receptors in addition to P2Y1R (17).…”
Section: Discussionmentioning
confidence: 74%
“…Finally, as is consistent with the notion that the smooth muscle relaxation is mediated by P2Y1R and is coupled to the activation of SK channels (13-15), we found that the relaxation response to Up4A in the colon, hyperpolarization responses in intact muscles, and outward currents activated in PDGFRα + cells were inhibited by SK-channel blockers. Up4A was more potent in inducing relaxation of colonic muscles than the well-known P2Y1R agonists ADP and ATP, the recently discovered neurotransmitter candidates NAD + and ADPR (14,15,17), and AMP and adenosine. The responses to even brief applications (i.e., 15-30 s) of Up4A were greater than the responses to equal concentrations of ATP and ADP, suggesting that the weaker effect of ATP and ADP cannot be attributed to ATP and ADP degradation to inactive (or less active) metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of these has greater or lesser affinity for the different purine receptors subtypes (31). It was recently hypothesized that β-NAD (β-nicotinamide adenine dinucleotide), ADPR (ADP ribose) or Up4A (uridine adenosine tetraphosphate) might be (even instead of ATP) the purinergic neurotransmitter in the GI tract (46)(47)(48)(49). However, some experimental data have nuanced these results (43,50-52).…”
Section: Atp and Maybe Other Neurotransmitters?mentioning
confidence: 91%